Teacher Parents Collaboration In Inclusive Education To Improve Well Being Of Special Needs Children - Lu-lu Tsamrotul Fuadah; Risbon Sianturi; Taopik Rahman; Ananda Aulia; Asti Septiani Rahmadani; Jingga Laila Masya (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2025)
This study aims to comprehensively examine the concept of inclusive education, the role of teachers, the role of parents, and the importance of collaboration between both parties in improving the well-being of children with special needs. This research employed a literature review method with a descriptive qualitative approach by analyzing 20 relevant sources consisting of scienfitic journal articles and academic books published within the last ten years. The analysis identified several major themes, including inclusive learning strategies, parental involvement, teacher competence, communication patterns between schools and families,and the impact of collaboration on chilfren’s academic, social and emotional development. The findings indicate that inclusive education has a positive impact on the overall well-being of children with special needs when supported by effective collaboration between teachers and parents. Teachers act as facilitators who design adaptive and inclusive learning strategies, while parents provide emotional support and learning motivation. However, the literature also reveals several dominant challenges, particularly limited communication, differences in understanding regarding inclusive education and inadequate educational resources and teacher training. Therefore, continuous efforts are needed to strengthen the collaboration between schools and families in supporting the successful implementation of  inclusive education.